FIELD STUDIES OF THE EFFECTIVENESS OF DIETARY SUPPLEMENTS WITH AIMED FUNCTIONAL PROPERTIES - Vekovcev A.A.; Podzorova G.A.; Kaz'mina A.Y.; Poznyakovskiy V.M. (Техника и технология пищевых производств, 2015)
The prevention of nutrition-related diseases is one of the priorities of state policy in the field of healthy nutrition of different popula-tion groups of the Russian Federation. The purpose of the current research is to study the role of nutrition factor in preventing widespread gastrointestinal and cardiovascular pathologies. The object of the research was a new form of biologically active additive(BAA) «Neurostabil», representing a complex of biologically active compounds and plant raw materials. Functional properties of thespecialized product are determined by the availability of vitamins C, A, E, D, B1, B2, B3, B6, B12, PP, folic acid, Biotin, peony root, hop cones, fragrant herbs and motherwort, alpha-glutamic acid in it. The results of clinical trials of the functional orientation and effectiveness of BAA have been obtained by its use in the treatment of patients with gastric ulcer, duodenal ulcer in combination with hypertension. Factors of acid-forming function, the dynamics of stomach endoscopic and morphological patterns, the amount of nu- cleic acids in duodenal and gastric aspirates, indices of psychosomatic disorders, clinical manifestations before and after complex dietetic therapy have been studied. The developed product proves to contribute to the correction of metabolic abnormalities of people suffering from the above diseases. The main vector of this influence is aimed at earlier relief of the major symptoms of a stomach ulcer and duodenal ulcer, stomach erosion epithelization, gastritis inflammation and activity reduction, the improvement of patient psycho-emotional condition. The most pronounced effect is observed when using BAA in combination with antisecretory drug an d eradication therapy. Methodological recommendations on the use of the specialized product at different stages of exacerbation have been developed.